2008
DOI: 10.1016/j.jfa.2008.07.021
|View full text |Cite
|
Sign up to set email alerts
|

A Karhunen–Loeve decomposition of a Gaussian process generated by independent pairs of exponential random variables

Abstract: We obtain the explicit Karhunen-Loeve decomposition of a Gaussian process generated as the limit of an empirical process based upon independent pairs of exponential random variables. The orthogonal eigenfunctions of the covariance kernel have simple expressions in terms of Jacobi polynomials. Statistical applications, in extreme value and reliability theory, include a Cramér-von Mises test of bivariate independence, whose null distribution and critical values are tabulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 43 publications
(50 reference statements)
0
18
0
Order By: Relevance
“…It also allows the modeler to choose regularity and self-similarity properties independently of each other, which offers more flexibility than the models considered in [11,10,38]. More examples of Gaussian self-similar process can be found in [8,18]. Interestingly, many of the Gaussian self-similar models share the same path regularity properties as fBm, because it can be shown that there are positive finite constants c, C for which c |t − s|…”
Section: Specific Motivations and Modeling Choicesmentioning
confidence: 99%
“…It also allows the modeler to choose regularity and self-similarity properties independently of each other, which offers more flexibility than the models considered in [11,10,38]. More examples of Gaussian self-similar process can be found in [8,18]. Interestingly, many of the Gaussian self-similar models share the same path regularity properties as fBm, because it can be shown that there are positive finite constants c, C for which c |t − s|…”
Section: Specific Motivations and Modeling Choicesmentioning
confidence: 99%
“…The spectral decomposition (1.2) is a useful tool in both theory and applications (see, e.g., [1], [16]). However explicit solutions to the eigenproblem (1.1) are notoriously hard to find and they are available only in special cases [12], [9,8], [21], [22,23], including the Brownian motion with K(s, t) = t ∧ s: λ n = 1 (n − 1 2 )π 2 and ϕ n (t) = √ 2 sin(n − 1 2 )πt (1.3) and the Brownian bridge with covariance function K(s, t) = s ∧ t − st: λ n = 1 πn 2 and ϕ n (t) = √ 2 sin πnt. (1.4) These formulas are obtained by reduction of the eigenproblem for integral operators to explicitly solvable boundary value problems for ordinary differential equations.…”
Section: Introductionmentioning
confidence: 99%
“…In 1982, he published a short book in French called "Probability, Chance and Certainty," destined for the educated general public (Deheuvels 1982), now in its fourth edition (Deheuvels 2008). This is a true intellectual tour de force.…”
Section: Advocate For Statisticsmentioning
confidence: 99%
“…The main aim of Deheuvels and Martynov (2008) was to enlarge the class of Gaussian processes for which an explicit Karhunen-Loeve decomposition may be computed (see also Pycke (2001)). This class is not so large.…”
Section: Brownian Quadratic Functionals With the Same Law (Deheuvels mentioning
confidence: 99%